Enhancing vocabulary mastery in senior high school students through short story reading: An experimental study - Murtiningsih, Sri Rejeki; Ilsanti, Anissa; Haryadi, Didit (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study explores the effectiveness of short stories as a teaching tool to enhance vocabulary mastery among senior high school students. The research involved 33 eleventh-grade social studies students from a public high school in Yogyakarta, Indonesia, using a one-group pretest-posttest experimental design. Over four class sessions, students engaged with short stories to improve their vocabulary. Vocabulary proficiency was assessed through tests administered before and after the intervention, with data analyzed using SPSS version 25. The pretest revealed a moderate vocabulary level, with an average score of 54.42. Post-intervention results showed significant improvement, with the average score increasing to 85.39. Statistical analysis yielded a t-value of 39.689, exceeding the critical t-value of 2.042, thus supporting the hypothesis (H1) that short story reading significantly enhances vocabulary mastery in EFL students.